Empowerment of Oyster Mushroom Farmers in Karangpring Village, Jember through Training on Making Oyster Mushroom Seeds F0, F1, and F2 - Ayu Puspita Arum; Setiyono Setiyono; Gatot Subroto (LP2M Universitas Jember, 2021)
Oyster mushroom farmers in KarangPring Village, Sukorambi District, Jember Regency have implemented the appropriate oyster mushroom cultivation technique. However, the profit of fresh oyster mushroom sales is still low because the production cost is very high due to F1 oyster mushroom seeds from the supplier being costly. Therefore, it is required a piece of knowledge about the production of F0, F1, and F2 oyster mushroom seeds. So that oyster mushroom farmers can produce oyster mushroom seeds independently. It will have an impact on the reduction of oyster mushroom's production costs. So, the profit of fresh oyster mushroom sales can also be increased; farmers can be F0, F1, and F2 oyster mushroom seed suppliers for others. The method of sharing F0, F1, and F2 oyster mushrooms production was training. The activity result was that the oyster mushroom farmers in Karangpring Village were capable of independently producing F0, F1, and F2 oyster mushroom seeds. These activities can be expected to reduce F0, F1, and F2 oyster mushrooms supply production costs. So the oyster mushroom farmers in KarangPring Village, Sukorambi District, Jember Regency can increase their profit from fresh oyster mushroom sales.